Control and ownership of assets within rural Ethiopian households - Fafchamps, Marcel; Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
There is renewed interest in the intrahousehold allocation of welfare, particularly among economists studying poor countries where even slight differences in the allocation of household resources can have dramatic consequences on child and female nutrition, morbidity, and mortality (Haddad and Hoddinott 1994; Rose 1999; Dercon and Krishnan 2000). The evidence collected so far tends to demonstrate that the allocation of consumption and leisure among household members varies systematically with their relative contributions to household total income (Thomas 1990; Alderman et al. 1995; Bourguignon, Browning, and Chiappori 1995). These results, however, provide no guidance about which policies affect intrahousehold outcomes. Various efforts have been made to fill this lacuna, focusing on the determinants of intrahousehold resource allocation. Some research has emphasized the influence that “threat points”—the utility each spouse has outside marriage—are likely to have on spouses’ bargaining power and hence on intrahousehold welfare (Manser and Brown 1980; McElroy and Horney 1981). If this approach is correct, one may hope to affect intrahousehold welfare by improving the “exit options” of disadvantaged groups.